Lexical and Syntactic Competency through Language Camp Activities Based on Multiple Intelligence Approach - Sasiwimon Sutthisan (International Journal of Pedagogy and Teacher Education, 2018)
The attempts of the present research were 1) to investigate the students’ problems in terms of lexical and syntactic usage in Language camp prior to the implementation of the activities based on multiple intelligence approach 2) to develop the students in terms of lexical and syntactic used in Language camp and 3) to compare the students’ learning achievement in terms of lexical and syntactic used in Language camp before and after implementing the activities based on multiple intelligence approach. The research sample, obtained by a purposive sampling technique, comprised 52 third-year students enrolled in Language Camp for English Skill Development course in the 2nd semester, Academic Year 2017. The research tools used in the study comprised of pre-and post-test, activities based on Multiple Intelligence approach, and standardized interview. The obtained quantitative data were computed by means, standard deviation, percentage, and independent sample t-test whereas the content analysis was done to elicit the qualitative data. The findings indicated that the students' problems of lexical and syntactic usage were categorized into two main issues: the confusion of using vocabularies and sentences and incorrect sentence orders. The results from the comparison before and after implementing the activities based on multiple intelligence approach revealed statistically significant differences at the .01 level. The students’ achievements were considerably improved after learning through the activities based on multiple intelligence approach and could employ each lexical and syntactic category with more confidence when retaking the exam.